2020
DOI: 10.59331/jasd.v3i3.139
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Returns of Sweet Melon Marketing in Bauchi and Gombe States, Nigeria

Abstract: The study examined the costs and returns of wholesale and retail sweet melon marketers in Bauchi and Gombe States, Nigeria. Multi-stage sampling technique was used to select 300 sweet melon and water melon marketers from 18 markets, 135 marketers were selected from Bauchi State and 165 from Gombe State. Data were collected using structured questionnaires. The result indicated that wholesale sweet melon marketers received the higher net income of N 629.16 and the total revenue of N 6163.68 in scarcity period, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…Household size is an important socioeconomic variable that determine the availability of family labour supply (Iheke et al, 2008). According to Mohammed et al (2013) in their study on economic analysis of cattle marketing in Gombe Metropolis, Nigeria reported that, householders are those individuals that are eating from the same pot and their consumption unit is equal to their production unit. Table 4 shows that, the mean household size of the farmers was 7.00 people.…”
Section: Results and Discussion Socio-economic Characteristics Of The...mentioning
confidence: 99%
“…Household size is an important socioeconomic variable that determine the availability of family labour supply (Iheke et al, 2008). According to Mohammed et al (2013) in their study on economic analysis of cattle marketing in Gombe Metropolis, Nigeria reported that, householders are those individuals that are eating from the same pot and their consumption unit is equal to their production unit. Table 4 shows that, the mean household size of the farmers was 7.00 people.…”
Section: Results and Discussion Socio-economic Characteristics Of The...mentioning
confidence: 99%